In Vitro Effect of Zirconia and Zirconia Enriched Glass Fiber Composite Posts on Fracture Resistance of Endodontically Treated Teeth - Zarbakhsh, Arash; Jalalian, Ezzatollah; Mazaheri Tehrani, Azita; Norozy, Mona; Fatourechi, Paniz (Journal of Dental School, 2019)
Objective: Despite the advantages of esthetic posts, lack of studies on their fracture resistance has limited their clinical use. This study aimed to compare the effect of two types of esthetic posts namely zirconia and zirconia enriched glass fiber composite posts on fracture resistance of endodontically treated teeth against compressive forces. Methods: This in vitro study was conducted on 20 mandibular premolar roots cut at the cementoenamel junction (CEJ). The roots were endodontically treated and randomly divided into 2 groups of 10. After post space preparation, in group 1 zirconia posts (CosmoPost, Ivoclar, Liechtenstein) and in group 2 zirconia enriched glass fiber composite posts (Ice Light, Danville, USA) were cemented in the roots using a dual-cure resin cement (Panavia F 2.0, Kuraray, Japan) according to the manufacturer’s instructions. The teeth were restored with composite resin cores (Lumiglass, RTD, France) using a prefabricated polyester matrix. After periodontal ligament (PDL) simulation by elastic polyether impression material (Impregum, 3M ESPE, USA), specimens were mounted in acrylic resin and subjected to 1195 Instron universal testing machine. Compressive load was applied at a 90° angle relative to the long axis of the teeth at a crosshead speed of 1mm/min until fracture. Since the data were normally distributed, t-test was used for statistical analysis. Results: The fracture resistance was 816.69 (120.89) N for zirconia posts and 843.76 (120.93) N for zirconia enriched glass fiber composite posts and these values were not significantly different (p=0.62). Fractures in group 2 were restorable. Conclusion: The fracture resistance of zirconia and zirconia enriched glass fiber composite posts was not significantly different and both types of posts can be successfully used.